Comprehensive analysis of spatial distribution of microplastics in Rawal Lake, Pakistan using trawl net and sieve sampling methods. (December 2022) - Nousheen, Rabia; Hashmi, Imran; Rittschof, Daniel; Capper, Angela
Abstract: Occurrence of microplastics (MPs) in freshwater environments, particularly reservoir and lakes, is an emerging concern. There are limited studies in Pakistan on microplastic pollution in the lacustrine environments and those that exist do not provide sufficient information on the spatial distribution of MPs in offshore surface water. The aims of this study were to determine microplastic abundance in Rawal Lake, Pakistan and to ascertain if sampling methodology influences microplastic counts. Surface water samples were collected from 10 sites; 5 tributaries, 2 human settlement and 3 fishing and boating areas using two different sampling techniques: 100 μm mesh trawl and 20 L sample through a 45 μm mesh sieve. A significant difference was observed in the abundance of MPs across two methods with the sieve method yielding 2.8 ± 1.44 particles/L and trawl yielding 0.025 ± 0.024 particles/L. Tributaries and boating/fishing area had higher microplastic abundance than the residential area regardless of sampling method. Filaments were the dominant shape of MPs in both type of samples followed by fragments in trawl samples and films in sieved samples. Microbeads were only detected in trawl samples. MPs within size range 0.1–0.9 mm were mostly fragments (82%). MPs were diverse in colors with white/transparent and black MPs common. Polypropylene was the main type of microplastic in Rawal Lake (40–74%). Scanning Electron Microscopy (SEM) of MPs showed cracks, roughness and striations on the particles. Energy Dispersive Spectroscopy (EDS) detected heavy metals (Fe, Cu, Ni, Pb, Zn, Co and Cr) in MPs. Findings suggest that microplastic pollution in Rawal Lake may pose great risk to aquatic and human life through leaching of inherent/adsorbed heavy metals and therefore requires future investigation. Graphical abstract: Image 1 Highlights: Sieve method (45 μm) yielded higher microplastic abundance than trawl net (100 μm). Tributaries and boating/fishing area in Rawal Lake had the highest MP abundance. Microplastics were mainly white/transparent or black, fibers and Polypropylene. Small microplastics (0.1–0.9 mm) were abundant and included mostly fragments. SEM-EDS detected partial weathering and heavy metals in microplastics.